SELULOSA DARI IMBAH CANGKANG KEMIRI SEBAGAI BAHAN PENGENTAL ALAMI BAHAN BAKAR - Rini Kartika Dewi; M. Istnaeny Hudha (IST AKPRIND Yogyakarta, 2018)
The gelling agent is a polymer component which is a combination of molecules that will give the desired thick and gel properties. The form of gel fuel can provide benefits in maintenance, is not dangerous, does not impact pollution and is practically handling. The source of thickener raw material that can potentially be derived from biomass. Because Inonesia is a country that is very rich in natural resources. In this study we tried to provide one biomass material that can be used as a thickening agent, namely cellulose from candlenut shell waste. In this study carried out by varying the mass of cellulose powder 1 shell candlenut waste; 2; 3; and 4 grams and 10 trichloroacetate concentrations; 15; 20 and 25%. Judging from the results of pH analysis, degree of substitution, viscosity, flame test and gas emission, the best mass of powdered candlenut thickener powder is found in the powder composition of 3 grams powder and the best trichloroacetate content at 15% level where the values ​​are based on powder mass and the best trichloroacetate content is the pH produced 8.4, with a substitution degree value of 0.29, a viscosity value of 1.43 cP, a flame test time of 4.19 minutes for ethanol gel combustion, with a value of CO gas emission 0.49 % ppm, the value of NOx gas emission produced is 0,0002% ppm, the value of gas emission of SO2 and gas H2S is 0% ppm.